(untitled) - Mizutani, Osamu (Tokyo, 1981)
This supplement to Japanese: The Spoken Languages in Japanese Life has been prepared to guide the instructor and the student step-by-step through the explanations of structure that are found in the main textbook. The question-and-answer format makes the material easier to follow by providing the questions that should be asked and accurate answers to them.
Keywords: Japanese language; Spoken Japanese